2020
DOI: 10.3389/fnins.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Sex Effect on Presurgical Language Mapping in Patients With a Brain Tumor

Abstract: Differences between males and females in brain development and in the organization and hemispheric lateralization of brain functions have been described, including in language. Sex differences in language organization may have important implications for language mapping performed to assess, and minimize neurosurgical risk to, language function. This study examined the effect of sex on the activation and functional connectivity of the brain, measured with presurgical functional magnetic resonance imaging (fMRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…The SMA controls functions during language processing in addition to its involvement in speech motor control [ 44 ]. SMA syndrome in which patients suffer from both motor and speech/language dysfunction is a common complication associated with dorsomedial prefrontal lesions and surgery [ 45 , 46 ]. Language deficits including impaired word retrieval have been linked to the disruption of the left frontal aslant tract primarily connecting the SMA to IFG in the left hemisphere [ 38 , 45 , 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SMA controls functions during language processing in addition to its involvement in speech motor control [ 44 ]. SMA syndrome in which patients suffer from both motor and speech/language dysfunction is a common complication associated with dorsomedial prefrontal lesions and surgery [ 45 , 46 ]. Language deficits including impaired word retrieval have been linked to the disruption of the left frontal aslant tract primarily connecting the SMA to IFG in the left hemisphere [ 38 , 45 , 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, it should be noted that handedness does not uniformly determine hemispheric dominance. In a recent language task functional MRI (fMRI) study, Yao et al ( 2020b ) measured handedness in 36 patients and identified two patients (5.6%) who were right-handed and show right hemispheric dominance. Therefore, we suggest that hemispheric dominance and/or the strict requirements of handedness be taken into account in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The complement system is a key mediator of immunity, meaning that dysregulation of this system directly implicates the immune system in the etiology of schizophrenia. Complement proteins are involved in neurogenesis, neuronal migration and synaptic formation ( 4 , 14 ), with C3 knockout mice showing synaptic elimination deficits ( 49 ) and impaired migration of neuroblasts ( 50 ). Early studies implicating complement system dysfunction in schizophrenia used hemolytic activity assays to measure overall complement component function in the blood ( 51 53 ).…”
Section: Mia Animal Modelsmentioning
confidence: 99%
“…Due to widely contradictory results, MIA animal models have been necessary to establish a causal relationship between MIA and schizophrenia-related abnormalities ( 10 13 ). These models have been pivotal in identifying molecular mechanisms that affect normal neurodevelopment in early life ( 10 ), most significantly changes to the complement system ( 4 , 14 ). These changes cause neuronal connectivity and synaptic pruning dysfunction which may contribute to pathological characteristics seen in post-mortem schizophrenic brains (e.g., decreased cortical gray matter thickness), leading to social deficits observed in schizophrenic patients ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%